2008
DOI: 10.1108/09727980810949142
|View full text |Cite
|
Sign up to set email alerts
|

Long run post issue performance of fixed price and book built IPOs: an empirical study on Indian markets

Abstract: Purpose: The purpose of this paper is to investigate empirically the difference in long run post issue performance of initial public offerings (IPOs) that tapped the Indian primary market through a fixed price offer and book building offer; also to assess the persistence of underperformance between these two routes of offering. Design/methodology/approach: The after market performance of the IPOs is empirically assessed based on their market prices and also taking into consideration the other factors associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…A similar result is depicted by the CAR when smaller windows around the announcements date have been taken. The outset of the present study is in line with Gopalaswamy et al (2008), Sinha & Gupta (2011) but in contrast with the studies conducted by Anand & Singh (2008) and Khan (2011).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A similar result is depicted by the CAR when smaller windows around the announcements date have been taken. The outset of the present study is in line with Gopalaswamy et al (2008), Sinha & Gupta (2011) but in contrast with the studies conducted by Anand & Singh (2008) and Khan (2011).…”
Section: Discussionsupporting
confidence: 86%
“…The merger announcement has a signi…cant and positive impact on the wealth of both bidders and targets the bank's shareholders in the Indian banking sector (Anand & Singh, 2008). However, in post-merger, the cumulative returns saw a downward trend implying a negative impact of the M&A (Gopalaswamy et al, 2008). From the …nancial performance point of view, in post-merger, the Indian acquiring …rms could generate synergy in the form of higher cash ‡ow, more business diversi…cation and cost-cutting (Kumar & Bansal, 2008).…”
Section: Review Of Literaturementioning
confidence: 99%
“…IPO underpricing over the years is ubiquitous phenomenon as observed in various studies (Krishnamurti and Kumar, 2002). Studies have also identified that short term over performance of IPOs of companies increases the expectations of potential investors and leads to a subsequent decline of long run performance (Bhatia and Singh, 2013; Gopalaswamy et al , 2008; Dhamija and Arora 2017a; Kohli, 2009; Mangala and Dhanda, 2019; Marisetty and Subrahmanyam, 2010; Mayur and Mittal, 2014). Contradicting this, Indian SME IPOs exhibit long-run over performance (Arora and Singh 2020b; Dhamija and Arora 2017c).…”
Section: Literature Reviewmentioning
confidence: 99%